Ultrasonic Assisted Extraction Of Etlingera Elatior Leaves, Optimization, Characterization And Kinetic Studies - Gong, Wee Jie (2020)
Etlingera elatior (E. elatior) is a herbaceous plant that is widely cultivated but the leaves are discarded as waste. Studies have shown that the leaves have potential in cosmetics formulation applications. In an extraction process, optimization and kinetic studies are important to develop a process that results in higher extraction yield and efficiency. In this study, the leaves extract of E. elatior were obtained by using ultrasonic-assisted extraction (UAE) technique. Methanol solvent was found to be most effective for extraction, followed by ethanol, acetone, ethyl acetate and n-hexane. The highest yield attained from UAE was 21.10 ± 0.29 % at an extraction time of 15 min, extraction temperature of 50 °C and liquid to solid (L/S) ratio of 35 mL/g at fixed ultrasonic power of 150 W. The UAE process was further optimized using response surface methodology by applying Box-Behnken design. The optimal conditions for the extraction were obtained at extraction time of 16 min, extraction temperature 55 °C and liquid to solid (L/S) ratio 38 mL/g and with methanol as solvent. Under these optimal conditions, the experimental yield of leaves extract obtained was 21.42 %, which matched well with the predicted model. Based on SEM images, ultrasonic treatment induced fissures on the surface of E. elatior leaves. For kinetics studies, Patricelli’s model fitted well to the extraction data with R2 > 0.99 and mean relative percentage deviation value of < 10 %. Among all solvent extracts of E. elatior leaves, methanolic extract exhibited the highest total phenolic content (228.35 ± 17.34 mg GAE/g) and has the highest antioxidant activity (IC50 value 66.25 ± 7.77 μg/mL). A reasonable correlation was found between antioxidant capacity and the TPC (R2= 0.75). All solvent extracts possess tyrosinase inhibition activity, but methanolic extracts showed the strongest tyrosinase inhibition activity (IC50 value 263.91 ± 13.61 μg/ml). Only methanolic and ethanolic extracts showed antibacterial activity towards B. subtilis (gram-positive bacteria), but none of the solvent extracts exhibited any antibacterial activity against E. coli (gram-negative bacteria). The study demonstrated that the properties of E. elatior leaves extract obtained by using UAE method may have potential for cosmeceutical applications.